Synthesis of curcumin-loaded chitosan phosphate nanoparticle and study of its cytotoxicity and antimicrobial activity. Issue 16 (1st November 2016) - Deka, C.; Aidew, L.; Devi, N.; Buragohain, A. K.; Kakati, D. K.
Abstract: Curcumin has acquired an important position in the treatment of various diseases. But its use, as a chemotherapeutic agent, is limited due to its low water solubility, poor bioavailability, and its sensitive nature at the physiological pH. To overcome this, curcumin was loaded into chitosan phosphate nanoparticles (CPNs). The loading efficiency was found to be 84%. DLS studies revealed the average particle size of CPNs and curcumin-loaded CPNs as 53 and 91 nm, respectively, and TEM results supplemented these values. A sustained release pattern was noticed and the amount of curcumin released in acidic pH was higher than at physiological pH. The curcumin nanoformulation exhibited proficient activity against both Gram-positive and Gram-negative bacteria as well as fungus. Cytocompatibility of the nanoformulations against peripheral blood mononuclear cells (PBMCs) and murine monocyte–macrophage cell line was confirmed by incubating with PBMCs and murine monocyte–macrophage cell line.